Association of Type of Antiepileptic Drugs and Serum Vitamin D Levels among People with Epilepsy - Adelia Putri Maharani; Hasna Syariva; Dwi Ngestiningsih; Arinta Puspita Wati; Santoso Jaeri (Diponegoro International Medical Journal, 2022)
Background: Epilepsy is a brain disease characterized by repeated unprovoked seizures at least two times with an interval of more than 24 hours between the first seizure and subsequent seizures. Valproic acid is an anti-seizure drug. Long-term use of valproic acid may be associated with metabolic disorders such as weight gain, and lipid profile changes, including vitamin D levels. Objectives: To determine the association of type of antiepileptic drugs and serum vitamin D levels among people with epilepsy.Methods: A cross-sectional study among 24 people with epilepsy was obtained from the outpatient clinic Diponegoro National Hospital Semarang. The subjects were then classified based on the type of antiepileptic drugs into two groups. The first group was subjects who used valproic acid (n=15) and the second group was subjects who used phenytoin (n=9). The demographic and clinical data were collected, then the measurement of vitamin D levels was performed using ELISA. The two independent samples T-test were performed to determine the differences of serum vitamin D levels among people with epilepsy.Results: The mean of serum vitamin D levels among 24 subjects were 17,32 + 6,37 ng/mL, and the mean of serum vitamin D levels based on the type of antiepileptic drugs were 16,92 + 4.27 ng/mL for the first group and 18 + 9.16 ng/mL for the second group. Furthermore that there was no significant difference in the serum vitamin D levels in both groups (p=0,697).Conclusion: There is no different effect of valproic acid and phenytoin on the serum vitamin D levels among people with epilepsy.